First record of red seabream, Pagrus major existence in the eastern Indian Ocean south of Java, Indonesia revealed by DNA barcoding - AGUS NURYANTO; DIAN BHAGAWATI; ELLY TUTI WINARNI; ASWI ANDRIASARI ROFIQOH (Society for Indonesian Biodiversity, 2023)
Abstract. Nuryanto A, Bhagawati D, Winarni ET, Rofiqoh AA. 2023. First record of red seabream, Pagrus major existence in the eastern Indian Ocean south of Java, Indonesia revealed by DNA barcoding. Biodiversitas 24: 6023-6030. The red seabream, Pagrus major, is widely believed to be mainly inhabited in the Northwest Pacific region. Although there are no previous studies reporting its existence in the Indian Ocean, a morphologically similar species of silver seabream, P. auratus, has been discovered. To comprehensively assess the geographical distribution of both species, there is a need to carry out a taxonomic study using DNA barcoding technique. Therefore, this study aimed to evaluate the taxonomic status of seabream (Sparidae) in the east Indian Ocean south of Java, Indonesia, using the cytochrome c oxidase 1 barcoding. Fish specimens were collected during the June to August 2023 field trips at fishing ports and auction centers along West Java and Banten southern coastlines. A total of 51 specimens were successfully barcoded and 99% genetic similarity was used as a species border. The results showed that three seabream species were identified, with intraspecific genetic similarity ranging from 99.77% to 100% and low genetic distance between 0.000 and 0.005 to one top hit conspecific. Furthermore, 21 specimens were identified as P. major with high genetic similarity ranging from 99.43% to 100% and genetic homology ranging from 99.44% to 100%. This discovery represented the first record of P. major in the east Indian Ocean, South Java, presenting essential data need for capture fisheries management in the region.